The European Registry on Obstetric Antiphospholipid Syndrome (EUROAPS): A survey of 247 consecutive cases - Alijotas-Reig, Jaume; Ferrer-Oliveras, Raquel; Ruffatti, Amelia; Tincani, Angela; Lefkou, Elmina; Bertero, Ma. Tiziana; Coloma-Bazan, Emmanuel; de Carolis, Sara; Espinosa, Gerard; Rovere-Querini, Patrizia; Kuzenko, Anna; Valverde, Enrique E.; et al. (Autoimmunity reviews, 2015)
To analyse the clinical features, laboratory data, foetal–maternal outcomes, and follow-up in a cohort of 247 women with obstetric antiphospholipid syndrome (OAPS). The European Registry on APS became a Registry within the framework of the European Forum on Antiphospholipid Antibody projects and placed on a website in June 2010. Cases with obstetric complaints related to aPL who tested positive for aPL prospectively and retrospectively were included. The three-year survey results are reported. 338 women with 1253 pregnancy episodes were included; 915 were historical and 338 were latest episodes. All these women tested positive for aPL. 247 of the 338 fulfilled the Sydney criteria. According to the laboratory categories, 84/247 were in category I, 42 in IIa, 66 in IIb and 55 in IIc. Obstetric complications other than foetal losses, appeared in 129 cases (52.2%). 192 (77.7%) had a live birth and 55 (22.3%) did not. The latter group of only 38 cases (69%) received adequate treatment and 17 (31%) did not. 177/247 (72%) women were put on heparin plus LDA. Thrombosis appeared in two during pregnancy and in 14 during the puerperium. 7 (3%) women evolved to complete SLE. OAPS shows differential characteristics than classical APS. All laboratory test categories are needed to avoid false-negative diagnoses. In some cases, complement levels could act as a serological marker. OAPS has very good foetal–maternal outcomes when treated. Thrombosis and progression to SLE in mothers with OAPS are scarce compared with “classical APS”, suggesting that they have different aPL-mediated pathogenic mechanisms.